Implementasi Nilai Nilai Kebangsaan Berbasis UUD 1945 Pada Analisis Pengaruh Ekspor Migas di Indonesia - Edy Soesanto; Mahesa Agung; Vandra Firmansyah Sukma (Jurnal Manajemen Bisnis Era Digital, 2024)
This study aims to analyze the effect of oil and gas exports on the Indonesian economy using the national values approach based on the 1945 Constitution. This research is motivated by the strategic role of the oil and gas sector in the national economy and the importance of implementing national values in the management and utilization of the oil and gas sector for the welfare of the people. The methodology used is analysis with data obtained from literature studies related to Indonesia's oil and gas exports. The results showed that oil and gas exports have a significant influence on the Indonesian economy, both in terms of state revenue, trade balance, and contribution to Gross Domestic Product (GDP). However, the management of the oil and gas sector still faces several challenges, including fluctuations in world oil prices, declining production, and environmental issues. The implementation of national values based on the 1945 Constitution in this analysis includes the principle of benefits for the people of Indonesia, sustainable management of natural resources, and equitable distribution of welfare. This study suggests that Indonesia's oil and gas export policy should be more directed towards strengthening national energy security, economic diversification, as well as implementing the principles of sustainable development and social justice in accordance with the values contained in the 1945 Constitution.